Studies on the penicillin- resistance with same enzyme characteristics and biochemicaı tests of staph. aureus isolated from cows milk with mastitis - İ. Yavuz SEZEN; Osman ERGANİŞ; Mehmet ÇORLU; Mehmet ATEŞ (Eurasian Journal of Veterinary Sciences)
Nineteen strains of Staph. aureus isolated from cows milk with mastitis were tested for their ability to produce coagulase, phosphatase, catalase, B-lactamase, clumping factor, oxydation/fermentcı. tion (O/F) and resistance of penicillin and ampicillin. All of the strains have produced B-lactamase and their resistance rates to penicillin and ampicillin were 94.9%, 47.9% respectively. Catalase, ı;ıhosphatase and 0/l<., producing rate of all Staph. aureus were positive 100%. The Coagulase tests found to be positive at the rate of 89.8% with rabbit plasma, 73.7% with cow plasma, 100% with mixture of rabbit-cow piasma. The rate of positive clumping factors was also found to be 89.8%, 94.9%, 100% with rabbit, cow and mix plasma, respectively. 73.7% of all strains have grown on Mannitol Salt Agar plates. 12 strains producedgolden cooured colonies. All of the 6 strains were intracutaneously inoculated to rabbits reduced necrosis.